ICT acceptance, investment and organization : cultural practices and values in the Arab world - Abdallah, Salam, 1958-; Albadri, Fayez (New York : Information Science Reference, 2011)
"This book is a unique source of information outlining the importance of Information Communication Technology (ICT) adoption and diffusion, covering the Arab world's strong need for access to information systems, while still paying close attention to their culture and localization of practices"--Provided by publisher.
Includes bibliographical references and index.
Keywords: sociology; Information technology -- Arab countries; Information technology -- Social aspects -- Arab countries